Characteristics of Herbal Tea Bags From a Mixture of Pandan Leaf Powder (Pandanus amaryfolius Roxb.) and Red Ginger (Zingiber officinale var. Rubrum) - Novelina, Novelina; Wellyalina, Wellyalina; Faramida, Shella (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This study investigated the effect of a mixture of pandan leaves and red ginger on the characteristics of herbal tea bags. Utilizing a completely randomized design (CRD) with 5 treatments and 3 replications, the data were statistically analyzed using ANOVA, followed by Duncan's New Multiple Range Test (DNMRT) at a 5% significance level. The treatments involved varying ratios of pandan leaves to red ginger: A (90:10 g), B (80:20 g), C (70:30 g), D (60:40 g), and E (50:50 g). Observations included tests for water content, ash content, polyphenol content, IC50 antioxidant activity, total plate count, and organoleptic properties. The results demonstrated that the mixture of pandan leaves, and red ginger significantly affected water content, ash content, total polyphenols, and IC50 antioxidant activity. Based on chemical, microbiological, and organoleptic analyses, treatment D (60:40 g) was identified as the optimal formulation, yielding the following values: water content (6.55%), ash content (4.44%), total polyphenols (28.63 mg GAE/g), antioxidant IC50 (100.31 ppm), total plate count (6.4 x 10^2), and organoleptic scores for color (3.70%), aroma (3.40%), and taste (3.10%).